Clearing the final hurdles to mitochondrial apoptosis: regulation post cytochrome C release - Monian, P.; Jiang, X. (Experimental Oncology, 2012)
In mammalian cells, the mitochondrial pathway of apoptosis plays a key role in various biological processes and has been extensively studied. One of the signature features of this pathway is permeabilization of the outer mitochondrial membrane (MOMP) and thus release of cytochrome c into the cytoplasm to trigger subsequent activation of executioner caspases. Because MOMP is associated with loss of mitochondrial function, it has long been believed to represent an irreversible commitment to cell death. However, emerging data over the last decade has indicated that induction of MOMP alone is not always sufficient to fully commit cells to death. As such, it becomes important to understand how apoptosis is regulated post-MOMP. Here we recount evidence investigating if and how cells can survive MOMP, and why this might have important physiological consequences. Furthermore, we review recent progress made in understanding how the pathway is regulated beyond MOMP and cytochrome c release. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.